2015
DOI: 10.1073/pnas.1509310112
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven generation of hydrogen: New chromophore dyads for increased activity based on Bodipy dye and Pt(diimine)(dithiolate) complexes

Abstract: New dyads consisting of a strongly absorbing Bodipy (dipyrromethene-BF 2 ) dye and a platinum diimine dithiolate (PtN 2 S 2 ) charge transfer (CT) chromophore have been synthesized and studied in the context of the light-driven generation of H 2 from aqueous protons. In these dyads, the Bodipy dye is bonded directly to the benzenedithiolate ligand of the PtN 2 S 2 CT chromophore. Each of the new dyads contains either a bipyridine (bpy) or phenanthroline (phen) diimine with an attached functional group that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 78 publications
1
45
0
Order By: Relevance
“…From the TA result, a 2.3 ps time constant was assigned for the singlet energy transfer from the bodipy unit to the ZnP moiety, comparable to those (i.e., 0.51–0.73 ps) of the reported bodipy‐conjugated PtN 2 S 2 PSs. In the bodipy‐PtN 2 S 2 systems, the bodipy‐antenna was an effective energy‐transfer chromophore towards the PtN 2 S 2 charge‐transfer moiety, increasing the H 2 production efficiency . Accordingly, our dyad design should make a positive contribution towards H 2 generation compared to ZnP alone.…”
Section: Resultsmentioning
confidence: 99%
“…From the TA result, a 2.3 ps time constant was assigned for the singlet energy transfer from the bodipy unit to the ZnP moiety, comparable to those (i.e., 0.51–0.73 ps) of the reported bodipy‐conjugated PtN 2 S 2 PSs. In the bodipy‐PtN 2 S 2 systems, the bodipy‐antenna was an effective energy‐transfer chromophore towards the PtN 2 S 2 charge‐transfer moiety, increasing the H 2 production efficiency . Accordingly, our dyad design should make a positive contribution towards H 2 generation compared to ZnP alone.…”
Section: Resultsmentioning
confidence: 99%
“…Further evidence for the important role of a triplet excited state was reported by the groups of Weare and Luo for intermolecular [16], as well as intramolecular [13,[15][16][17] BODIPY-cobaloxime systems. More recently, Eisenberg et al have used a combination of strongly light-absorbing BODIPYs and platinum diamine dithiolate charge transfer chromophores for sensitizing TiO2 in light-driven reduction of aqueous protons [18,19]. A survey of the combined influence of BODIPY halogenation and introduction of sterically-demanding aryl groups on photocatalytic hydrogen production activity was presented by the same authors, showing the presence of a pronounced heavy atom effect as well as an enhanced dye stability with an increase in steric demand at the meso position [20].…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, alternative semiconductor materials have been identified that effectively harvest sunlight and split water more efficiently (4,5); however, the associated costs are not economically competitive with today's fossil fuels. In a step toward simple low-cost approaches to solar hydrogen generation, Zheng et al (6) report sustained H 2(g) generation over periods of 12 d with ∼40,000 turnovers by a dye molecule anchored to TiO 2 /Pt particles in an aqueous suspension. The turnover numbers are unprecedented for solar fuel production and may enable practically useful molecular approaches to solar hydrogen production.…”
mentioning
confidence: 99%
“…Light absorption by "dyads" drives the newly discovered hydrogen generation (6). The particular dyad that proved to be the most efficient is shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation